The effects of cast-related training for nurses on the quality of cast care: A quasi-experimental study. (August 2020) - Mokhtari, Razieh; Adib-Hajbaghery, Mohsen; Rezaei, Mahboubeh
Abstract: Introduction: Quality cast application and care is among the nursing skills which require competence, knowledge, and expertise. This study aimed to assess the effects of cast-related training for nurses on the quality of pre-, intra- and post-casting care. Methods: This quasi-experimental study was conducted in 2018 in two phases: before and after a cast-related training for nurses involved in cast application and care. In the first phase, 94 patients with a cast were assessed for pre- intra- and post-casting care quality. In the second phase, after the training program, the same number of new patients were assessed. Study data were collected using a 57-item checklist with items on; patient preparation, cast application, and post-casting care including patient education. Descriptive statistics, Fisher's exact, and independent-samples t-tests were used to analyze the data. Results: The mean pre-casting care score significantly increased from 1.39 ± 0.16 at baseline to 1.69 ± 0.32 after the intervention (P = 0.001). The mean intra-casting care score increased from 1.42 ± 0.31 at baseline to 1.52 ± 0.17 after the intervention (P = 0.014). However, the study intervention did not improve the mean post-casting care score. Conclusion: This training program improved the quality of pre- and intra-casting care, but did not improve the post-casting care and care measures related to patient education. Therefore, regular in-service training programs for nurses are recommended to improve their knowledge, skills, and performance in cast- pplication and care.